The broadcast century and beyond a biography of American broadcasting - Hilliard, Robert L. 1925- (Focal Press, 2005)
The Broadcast Century and Beyond, 4th Edition, is a popular history of the most influential and innovative industry of the previous and current century. The story of broadcasting is told in a direct and informal style, blending personal insight and authoritative scholarship to fully capture the many facets of this dynamic industry. The book vividly depicts the events, people, programs, and companies that made television and radio dominant forms of communication. The ability of radio and television to educate, enlighten, and stimulate the contemporary mind is perh.
Includes bibliographical references (pages 341-344) and index. - Print version record
Keywords: Broadcasting -- History -- United States; Broadcasting -- Biography -- United States; Radiodiffusion; États-Unis; Histoire; BIOGRAPHY & AUTOBIOGRAPHY; General; BUSINESS & ECONOMICS; Industries; Media & Communications; TECHNOLOGY & ENGINEERING; Telecommunications; Broadcasting; United States; Biographies; History; Biography